Governance Networks and Second Home Tourism: Insights from a Sun and Sea Destination - D’Emery, Raphael; Pinto, Hugo; Ribeiro Almeida, Cláudia (Journal of Tourism, Sustainability and Well-being, 2018)
Second home tourism obtained in recent years a relevant attention in Portugal and was identified by the national tourism plan as one of the strategic products for the country. In the Algarve its weight is relevant for the tourism dynamics. The study presents a qualitative analysis to identify the perspectives and tensions between different actors in this Portuguese region. A network analysis offers an interesting output of the cooperation dynamics among these actors. The results are helpful to understand second home tourism trajectories and present useful information for future strategies and plans for regional development. Effective governance in second home tourism may offer an opportunity for increasing the destination’s attractiveness, both for tourists and investors.